2012
DOI: 10.1007/s00281-012-0311-2
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and clinical presentations of celiac disease

Abstract: Evidence of the prevalence of celiac disease comes from serological screening studies. These have revealed that celiac disease is common, occurring in about 1 % of the population worldwide. There are some countries with higher prevalence rates such as Finland and others with lower rates, for example Germany. The disease is found in most continents and appears to be increasing. Most people with the disease are not currently diagnosed though women are diagnosed more frequently than men. The mode of presentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
67
2
9

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(81 citation statements)
references
References 105 publications
3
67
2
9
Order By: Relevance
“…The present study results differ from those reported by Reilly & Green 6 and Ukkola et al 12 , who found that the clinical picture of celiac disease has changed both in children and adults as diarrhea and malabsorption are increasingly uncommon (classical gastrointestinal symptoms). Currently, abdominal cramps and delayed growth are the main manifestations in children.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…The present study results differ from those reported by Reilly & Green 6 and Ukkola et al 12 , who found that the clinical picture of celiac disease has changed both in children and adults as diarrhea and malabsorption are increasingly uncommon (classical gastrointestinal symptoms). Currently, abdominal cramps and delayed growth are the main manifestations in children.…”
Section: Discussioncontrasting
confidence: 57%
“…Reilly & Green 6 also affirmed that the highest prevalences of celiac disease have occurred in adult females, and that celiac disease has mostly been diagnosed in later life 6 . In addition Araújo 19 and Polanco 20 found that celiac disease is more common in women, and the latter reported that celiac disease affects women in a ratio of 2 to 1 19,20 .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…In literature this percentage is referred to as 'tip of the iceberg' . Unfortunately, it is impossible to acquire specific data as there is no official record of the number of people affected by celiac disease [1][2][3].…”
Section: Celiac Disease-the Tip Of the Icebergmentioning
confidence: 99%